2012
DOI: 10.1002/pon.3159
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive functioning in allogeneic hematopoietic stem cell transplantation recipients and its medical correlates: a prospective multicenter study

Abstract: Below average cognitive performance is common in this patient group. In addition, a subgroup shows reliable cognitive decline after allogeneic HSCT. Healthcare professionals should be aware of these treatment-related cognitive side effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
63
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(73 citation statements)
references
References 33 publications
7
63
1
1
Order By: Relevance
“…All patients completed the set of questionnaires at home and brought them to the scheduled oncology follow-up appointment at the Department of Stem Cell Transplantation, where also the neuropsychological assessment was performed (data published elsewhere). 16 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All patients completed the set of questionnaires at home and brought them to the scheduled oncology follow-up appointment at the Department of Stem Cell Transplantation, where also the neuropsychological assessment was performed (data published elsewhere). 16 …”
Section: Methodsmentioning
confidence: 99%
“…16 Patients were recruited from six German university medical centers in Hamburg, Hannover, Dresden, Kiel, Essen and Munich and were assessed before conditioning/at admission (pre-HSCT), 100 ± 20 days after allogeneic HSCT (100 days after HSCT) and 12 ± 1 months after HSCT (1 year following HSCT). Data were collected over a 3-year period from June 2005 to July 2008.…”
Section: Methodsmentioning
confidence: 99%
“…Newer therapeutic modalities are also associated with adverse cognitive outcomes. Allogeneic hematopoietic stem cell transplantation is associated with risk of temporary cognitive disability [49]. Patients before allogeneic hematopoietic stem cell transplantation may show slow word fluency and impairment on cognitive domains, while after transplantation they may exhibit fine motor dysfunction and delayed verbal answering [49].…”
Section: Consequences Of the Hypothesis And Discussionmentioning
confidence: 99%
“…Also Sherwart et al, reported cognitive dysfunction pre-and post HSCT in 102 patients [11]. Before and after transplantation 50% performed below tests norms.…”
Section: Cognitive Impairment Associated With Hematopoietic Cell Tranmentioning
confidence: 99%